EKSPLORASI KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPS DI MTS SKB 3 MENTERI - Simbolon, Ferdinan Aryadi (Islamijah: Journal of Islamic Social Sciences, 2024)
The lack of critical thinking of students, especially social studies subjects at MTs SKB 3 Minister Lubuk Bayas Perbaungan District is certainly caused by various factors, one of which is the lack of learning models applied by teachers to improve students' critical thinking skills. Based on the explanation above, the author feels the need to examine the problem and make it as a final project with the title “Critical Thinking Ability of Students in Social Studies Learning at MTs SKB 3 Minister Lubuk Bayas Perbaungan District. The purpose of this study was to determine whether or not the critical thinking skills of students in social studies learning at MTs SKB 3 Minister Lubuk Bayas Perbaungan District. Efforts made in improving students' critical thinking skills in social studies learning at MTS SKB 3 Minister Lubuk Bayas Perbaungan Subdistrict is to use effective methods to adapt the method to the material being taught and the method of question and answer and group discussion. Thus the critical thinking skills of students will increase.